Նեմեսիոս Եմեսացու «Յաղագս բնութեան մարդոյ» երկի միջնադարյան հայ մեկնությունները - Մոսիկյան, Կարինե
Medieval Armenian literature is rich in commentaries on philosophical works. There exist several Armenian commentaries on On the Nature of Man by the Greek philosopher Nemesius of Emesa. The extant commentaries are the following: 1. Commentary on the Book of Nature, 2. Analysis of the Book of Nature, 3. Ms M621, bearing the general title Book of Causes and Analyses, contains two different commentaries: Analysis of the Commentary on the Book of Nature and Commentary on the Book of Nature. The last two writings are different from the first and the second. The manuscripts which contain Nemesius’ work often have short marginal explanations and notes. Scholars (Garegin Zarbhanalean, Ghewond Alishan, At‘anēs Tiroyean) have attributed some of them to Grigor Skevṛats‘i. Nothing is known about the authors of the other commentaries but the historian of medicine Levon Hovhannisyan is sure they are original Armenian works, since there is no mention of commentaries on the Book of Nature in the Greek sources. The author of this article has made an attempt to collect and analyze all the existent data and suppositions, as well as to offer new hypotheses. В армянской средневековой литературе часто встречаются комментарии философских сочинений. Произведение греческого философа Немесия О природе человека армянские авторы толковали не раз. До нас дошли следующие комментарии: 1. “Толкование на книгу о природе”; 2. “Анализ книги о при- роде”; 3. Два разных комментария дошли до нас в рукописи М 621, носящей общий заголовок “Книга причин и анализа”: “Анализ толкования книги о природе” и “Толкование на книгу о природе”. Они отличаются от первого и второго сочинения. На полях рукописей, содержащих “О природе человека”, встречаются также краткие заметки и пояснения. Некоторые такие записи филологи (Гарегин Зарбаналян, Гевонд Алишан и Атанас Тироян) приписывали Григорию Скевраци. Об авторах остальных комментариев ничего не известно, однако историк медицины Левон Оганесян утверждает, что они написаны на армянской почве, так как в греческих источниках нет упоминаний о комментариях на книгу «О природе». В статье сделана попытка собрать воедино и проанализировать все наличные факты и предположения, предложить новые гипотезы.
Keywords: Բանասիրություն